2021
DOI: 10.3389/fnmol.2021.699574
|View full text |Cite
|
Sign up to set email alerts
|

Application of Trio-Whole Exome Sequencing in Genetic Diagnosis and Therapy in Chinese Children With Epilepsy

Abstract: Epilepsy is one of the most common neurological disorders in pediatric patients with other underlying neurological defects. Identifying the underlying etiology is crucial for better management of the disorder. We performed trio-whole exome sequencing in 221 pediatric patients with epilepsy. Probands were divided into seizures with developmental delay/intellectual disability (DD/ID) and seizures without DD/ID groups. Pathogenic (P) or likely pathogenic (LP) variants were identified in 71/110 (64.5%) patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Additionally, six splicing mutations Dental anomalies: illustrative images from the selected patients showing teeth defects and malformations in both groups of young patients with primary teeth and older patients with permanent teeth, as well as open anterior-skeletal bite and overgrowth of the gingiva. (13-21), four small deletions (18,20,(22)(23)(24)(25)(26), two small insertions (6,12,13,16,27,28), and four gross deletions (13,20,29) have been reported. These pathogenic variants have been linked to various phenotypes, especially seizure-causing syndromes such as Kohlschütter-Tönz and West syndromes (19, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, six splicing mutations Dental anomalies: illustrative images from the selected patients showing teeth defects and malformations in both groups of young patients with primary teeth and older patients with permanent teeth, as well as open anterior-skeletal bite and overgrowth of the gingiva. (13-21), four small deletions (18,20,(22)(23)(24)(25)(26), two small insertions (6,12,13,16,27,28), and four gross deletions (13,20,29) have been reported. These pathogenic variants have been linked to various phenotypes, especially seizure-causing syndromes such as Kohlschütter-Tönz and West syndromes (19, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Sinus bradycardia in the resting state has been reported in some RYR2 mutation carriers and in phenotypically affected CPVT patients (7). Recently, interictal arrhythmias was found in case 3 of BECTS identified with RYR2 c.8574G > A, and case 5 with compound heterozygous missense mutation (RYR2 c.7469T > C and c.12770G > A) presented sinus arrhythmia with mild cardiac structural abnormalities, and showing abnormal sinus arrhythmia, ventricular extrasystoles, and paroxysmal ventricular tachycardia (32). In the present study, ECG showed sinus tachycardia in proband and his mother without phenotypic effects, rather than sinus bradycardia as reported in RYR2 mutation carriers, but it was consistent with the case reported by Jiang.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang T et al reported a child with generalized epilepsy carried a heterozygous missense mutation of RYR2 [c.14767A > T/ p . (Met4923Leu)], showing abnormal sinus arrhythmia, ventricular extrasystoles, and paroxysmal ventricular tachycardia ( 32 ). In the present study, ECG showed sinus tachycardia in proband and his mother without phenotypic effects, rather than sinus bradycardia as reported in RYR2 mutation carriers, but it was consistent with the case reported by Jiang.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an important challenge for researchers and clinicians nowadays in investigating rare disorders involves predicting pathogenicity for VUS. With several guidelines mentioned for predicting the pathogenicity of variants [8,47,48], molecular investigators face a daunting task in considering a rare variant as benign or pathogenic and inferring it to be pathogenic. In explaining the germline/heritability of complex variants based on the rare variant hypothesis, we argue that the extreme rare variants are associated with phenotype sampling [49].…”
Section: Variants Of Unknown Significancementioning
confidence: 99%
“…To check this, parent-child trios/quad WES analysis could be a powerful approach, although biases impede the identification of potential de novo mutations. Nevertheless, a majority of mutations may not transcend from parent to offspring, making it necessary to comprehensively analyze genetic variants in order to confirming them as associated [8]. Trio-based exome sequencing has provided beneficial for identifying de novo variants in rare diseases, attributing them to largely heterozygous/causal mutations [9].…”
Section: Introductionmentioning
confidence: 99%